Who is the Mystery Reader? - Willems, Mo (New York : Hyperion Books For Children, 2019)
As Zoom Squirrel and his friends try to identify the Mystery Reader, they learn about books, how they are written, and how to read--while sharing a-corny jokes.
Accelerated Reader
bt/mm2
Keywords: Books and reading -- Juvenile fiction; Squirrels -- Juvenile fiction; Acorns -- Juvenile fiction; Jokes -- Juvenile fiction; Wit and humor -- Juvenile fiction; Detective and mystery stories -- Juvenile literature; Humorous stories; Books and reading -- Fiction; Squirrels -- Fiction; Acorns -- Fiction; Jokes -- Fiction; Wit and humor -- Fiction; Mystery and detective stories; Humorous fiction